2024
DOI: 10.3390/metabo14030156
|View full text |Cite
|
Sign up to set email alerts
|

Daily Injection of the β2 Adrenergic Agonist Clenbuterol Improved Muscle Glucose Metabolism, Glucose-Stimulated Insulin Secretion, and Hyperlipidemia in Juvenile Lambs Following Heat-Stress-Induced Intrauterine Growth Restriction

Rachel L. Gibbs,
James A. Wilson,
Rebecca M. Swanson
et al.

Abstract: Stress-induced fetal programming diminishes β2 adrenergic tone, which coincides with intrauterine growth restriction (IUGR) and lifelong metabolic dysfunction. We determined if stimulating β2 adrenergic activity in IUGR-born lambs would improve metabolic outcomes. IUGR lambs that received daily injections of saline or the β2 agonist clenbuterol from birth to 60 days were compared with controls from pair-fed thermoneutral pregnancies. As juveniles, IUGR lambs exhibited systemic inflammation and robust metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Fetal hypoxemia is resolved by birth, and circulating monocyte numbers consequently return to normal in IUGR offspring [24]. However, we recently found that blood cytokine concentrations remained elevated well after birth [24,25], which is consistent with the programming of a more inflammatory phenotype in IUGR monocytes [59]. In the present study, systemic inflammation in IUGR fetuses also coincided with a 42% reduction in circulating concentrations of the anti-inflammatory ω-3 PUFA eicosapentaenoic acid, which was presumably a product of stress-impaired ∆5 and ∆6 desaturase activity, as previously observed [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fetal hypoxemia is resolved by birth, and circulating monocyte numbers consequently return to normal in IUGR offspring [24]. However, we recently found that blood cytokine concentrations remained elevated well after birth [24,25], which is consistent with the programming of a more inflammatory phenotype in IUGR monocytes [59]. In the present study, systemic inflammation in IUGR fetuses also coincided with a 42% reduction in circulating concentrations of the anti-inflammatory ω-3 PUFA eicosapentaenoic acid, which was presumably a product of stress-impaired ∆5 and ∆6 desaturase activity, as previously observed [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed at the University of Nebraska-Lincoln, which is accredited by AAALAC International. After a 7-day acclimation period, Polypay ewes (2 to 4 years of age; 72.7 ± 0.4 kg; 2.5 to 3 body condition score) were timed-mated to a single Polypay male and heat-stressed to produce placental insufficiency-induced IUGR fetuses, as previously described [ 25 , 42 ]. Briefly, ewes carrying singleton or twin pregnancies were housed under ambient conditions of 40 °C and 35% relative humidity (86 temperature–humidity index per [ 43 ]) from the 40th to the 95th day of gestational age (dGA) and were then returned to thermoneutral conditions (25 °C, 35% relative humidity, 70 temperature–humidity index) for the duration of the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations